Scene-based control method - DU YANYAN; ZHANG HUANRONG; MA XUZONG (2017)
The invention provides a scene-based control method and belongs to the field of smart home. The control method includes: allowing control equipment to receive the attribute parameters of drive equipment, saving the attribute parameters into the control equipment, associating the attribute parameters with a preset button arranged on the control equipment, triggering the preset button, and transmitting a control instruction corresponding to the drive equipment. The scene-based control method has the advantages that scene configuration can be reversely added into a control end from a to-be-controlled end, the problem that user needs to face cold data in an original configuration manner can be avoided, configuration operation is the same as the user sees, and the experience of the whole scene configuration is improved. 本发明提供了基于场景的控制方法，属于智能家居领域，包括令控制设备接收驱动设备的属性参数，将属性参数保存至控制设备，并将属性参数与设置在控制设备上的预设按键相关联，触发预设按键，发送与驱动设备对应的控制指令。通过将场景的配置可以从被控端反向加入到控制端中，这种方法可以避开原有配置方式中用户需要面对冰冷的数据的问题，实现配置操作所见即所得，提升了整个场景配置的体验度。